Secondary battery and electric device
By introducing grooves on the positive electrode active material layer of the lithium-ion battery and controlling related parameters, the problems of poor conductivity, low energy density and poor circulation performance are solved, and a secondary battery with high energy density, low internal resistance and excellent circulation performance are achieved.
Patent Information
- Application Number
- CN202411844638.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
AI Technical Summary
The poor conductivity, low energy density and poor circulation performance of existing lithium-ion batteries limit their commercialization process.
By introducing grooves on the positive electrode active material layer and reasonably controlling the porosity, thickness, unit area capacity and groove depth of the positive electrode active material layer, the positive electrode sheet meets a specific parameter range, thereby improving the overall performance of the secondary battery.
The secondary battery has high energy density, excellent cycling performance, low internal resistance and good fast charging performance.
Smart Images

Figure BDA0005188980840000131 
Figure BDA0005188980840000141 
Figure BDA0005188980840000142
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, in particular to a secondary battery and an electrical device. Background Art
[0002] In order to meet the needs of energy storage systems and electric vehicle markets for high energy density and fast charging, lithium-ion batteries with both high energy and high power density have received widespread attention. x Fe 1-x PO4, LMFP) is a highly promising lithium-ion battery cathode material with high safety and theoretical energy density, but its poor conductivity leads to its poor fast charging capability and the actual energy density of lithium manganese iron phosphate battery is far from the theoretical energy density, which seriously restricts its commercialization process. Summary of the invention
[0003] The purpose of this application is to solve the problems of poor conductivity, low energy density and poor cycle performance of secondary batteries in the prior art, and to provide a secondary battery and an electrical device with high energy density, good conductivity, low internal resistance and excellent cycle performance.
[0004] To achieve the above-mentioned object, the first aspect of the present application provides a secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the positive electrode active material layer has a groove;
[0005] The positive electrode sheet satisfies: 32≤Y≤70,
[0006] Where, Y = ε × (300-d) / 2 + 2 × (12-C) + 0.5h;
[0007] ε is the porosity of the positive electrode active material layer;
[0008] dμm is the thickness of the positive electrode active material layer;
[0009] C mAh / cm 2 is the capacity per unit area of the positive electrode;
[0010] hμm is the depth of the grooves in the positive electrode active material layer.
[0011] As an embodiment of the present application, the porosity ε of the positive electrode active material layer is 25% to 50%.
[0012] As an embodiment of the present application, the double-sided thickness d μm of the positive electrode active material layer is 190 μm to 230 μm.
[0013] As an embodiment of the present application, the capacity per unit area of the positive electrode sheet is C mAh / cm 2 5.5 mAh / cm 2 ~7mAh / cm 2 .
[0014] As an embodiment of the present application, the depth h μm of the grooves of the positive electrode active material layer is 30 μm to 60 μm.
[0015] As an embodiment of the present application, 25%≤Z≤65%, wherein Z=2h / d.
[0016] As an embodiment of the present application, the negative electrode active material layer has grooves.
[0017] As an embodiment of the present application, the depth of the grooves on the negative electrode active material layer is 10 μm to 30 μm.
[0018] As an implementation scheme of the present application, the direction parallel to the positive electrode tab is the longitudinal direction, the distribution state of the grooves in the positive electrode active material layer or the negative electrode active material is the longitudinal distribution, and the spacing of the grooves is 2 mm to 5 mm.
[0019] As an implementation scheme of the present application, the length of the groove is 20 mm to 90 mm, and the width is 0.05 mm to 0.2 mm.
[0020] As an embodiment of the present application, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes lithium manganese iron phosphate and a ternary material;
[0021] The ternary material includes lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide, wherein the lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide is Li a Ni b Co c X d Q e O2; wherein, 0.9≤a≤1.1, 0.3≤b<1, 0<c<1, 0<d<1, 0≤e≤0.1, b+c+d+e=1, X is Mn or Al, and Q is at least one of Zr, Al, Mn, Zn, Cu, Cr, Mg, Fe, V, W, Y, Nb, Ti, In, La, Ce, Sr, Sb, and B.
[0022] As an embodiment of the present application, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes graphite.
[0023] As an implementation scheme of the present application, the Dv50 particle size of the lithium manganese iron phosphate is 0.4 μm to 1.6 μm.
[0024] As an implementation scheme of the present application, the Dv50 particle size of the ternary material is 0.6 μm to 2 μm.
[0025] In a second aspect of the present application, an electrical device is provided, comprising the secondary battery described above.
[0026] Compared with the prior art, the beneficial effects of this application are:
[0027] The secondary battery provided by the present application introduces grooves on the positive electrode active material layer and reasonably controls the porosity of the positive electrode active material layer, the thickness of the positive electrode active material layer, the capacity per unit area of the positive electrode pole piece and the depth of the grooves of the positive electrode active material layer, so that the positive electrode pole piece satisfies: 32≤ε×(300-d) / 2+2×(12-C)+0.5h≤70, thereby comprehensively improving the comprehensive performance of the secondary battery, achieving excellent cycle performance, lower internal resistance and higher energy density as well as good fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of a top view of the positive electrode active material layer in Example 1;
[0029] Figure 2 This is a schematic top view of the positive electrode active material layer in Example 20. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0031] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0032] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0033] In one embodiment of the present application, the present application proposes a secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; and the positive electrode active material layer has a groove;
[0034] The positive electrode sheet satisfies: 32≤Y≤70,
[0035] Where, Y = ε × (300-d) / 2 + 2 × (12-C) + 0.5h;
[0036] ε is the porosity of the positive electrode active material layer;
[0037] dμm is the thickness of the positive electrode active material layer;
[0038] C mAh / cm 2 is the capacity per unit area of the positive electrode;
[0039] hμm is the depth of the grooves in the positive electrode active material layer.
[0040] Specifically, in the present application, when positive electrode active material layers are disposed on both sides of the positive electrode current collector, the thickness of the positive electrode active material layer is the sum of the thicknesses of the two positive electrode active material layers.
[0041] The present application study found that after introducing grooves on the positive electrode active material layer, the porosity of the positive electrode active material layer, the thickness of the positive electrode active material layer, the capacity per unit area of the positive electrode pole piece and the depth of the grooves of the positive electrode active material layer are further reasonably controlled, so that the positive electrode pole piece satisfies: 32≤ε×(300-d) / 2+2×(12-C)+0.5h≤70, which can effectively improve the cycle performance and fast charging performance of the secondary battery, reduce the internal resistance of the secondary battery, and improve the energy density of the secondary battery.
[0042] Specifically, on the first aspect, the present application introduces grooves on the positive electrode active material layer, which can effectively shorten the bending distance of lithium ion migration, is conducive to the efficient diffusion of lithium ions, reduces the internal resistance of the secondary battery, and improves the fast charging capability of the secondary battery; on the second aspect, the relationship between the porosity of the positive electrode active material layer and the depth of the grooves of the positive electrode active material layer is limited, and more vertical space can be provided by designing the pores / channels inside the electrode, thereby increasing the electrode porosity and reducing the tortuosity. According to the relationship between the effective ion diffusion coefficient Deff and the porosity ε of the positive electrode active material layer and the tortuosity, it can be seen that the electrode sheet design of the present application can make lithium ions diffuse more efficiently, thereby effectively shortening the tortuosity distance of lithium ion migration; on the third aspect, the capacity per unit area of the positive electrode sheet and the thickness of the positive electrode active material layer are closely related to the energy density of the secondary battery. At the same time, the porosity of the positive electrode active material layer and the depth of the grooves of the positive electrode active material layer are related to the bending distance of lithium ion migration, thereby affecting the efficient diffusion of lithium ions; by establishing the relationship between the above parameters, the present application can effectively improve the energy density and cycle performance of the secondary battery and reduce the internal resistance of the secondary battery.
[0043] Exemplarily, the positive electrode plate satisfies: 32≤Y≤70, where Y can be any point value or any two point range values between 32 and 70, for example, it can be one of 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 60, 62, 64, 66, 68, 70 or any two range values.
[0044] In one embodiment, the positive electrode sheet satisfies: 40≤Y≤58. For example, Y can be a range of one or any two of 40, 41, 43, 45, 47, 49, 51, 53, 55, 57, and 58.
[0045] The present application study found that the value range of Y in the relationship satisfied by the positive electrode plate will affect the comprehensive performance of the secondary battery. When the positive electrode plate is further selected to satisfy: 40≤Y≤58, the comprehensive performance of the secondary battery obtained is better.
[0046] In one embodiment, the porosity ε of the positive electrode active material layer is 25% to 50%.
[0047] It should be noted that the test method for the porosity of the positive electrode active material layer is: using a true density meter hexadecane absorption method to measure the electrode porosity.
[0048] The porosity of the positive electrode active material layer can be adjusted by adjusting the groove depth h.
[0049] Exemplarily, the porosity ε of the positive electrode active material layer may be any point value or any two point range values between 25% and 50%, for example, it may be one of 25%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50% or any two range values.
[0050] The present application study found that the porosity of the positive electrode active material layer affects the wetting effect of the electrolyte in the secondary battery, and also affects the diffusion capacity of lithium ions, thereby affecting the cycle performance, internal resistance and fast charging performance of the secondary battery. When the porosity ε of the positive electrode active material layer is further selected to be 25% to 50%, the secondary battery obtained has a lower internal resistance, better cycle performance and better fast charging performance.
[0051] In one embodiment, the porosity ε of the positive electrode active material layer is 35% to 45%. For example, the porosity ε of the positive electrode active material layer can be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, or any two of them. The present application has found that when the porosity ε of the positive electrode active material layer is further selected to be 35% to 45%, the comprehensive performance of the secondary battery obtained is better.
[0052] In one embodiment, the double-sided thickness d μm of the positive electrode active material layer is 190 μm to 230 μm.
[0053] It should be noted that the test method for the double-sided thickness of the positive electrode active material layer is: using a laser measuring instrument to measure the thickness.
[0054] The thickness of the positive electrode active material layer on both sides can be controlled by the amount of the positive electrode slurry applied.
[0055] Exemplarily, the double-sided thickness dμm of the positive electrode active material layer may be any point value or any two point range values between 190μm and 230μm, for example, it may be one of 190μm, 195μm, 200μm, 205μm, 210μm, 215μm, 220μm, 225μm, 230μm or any two range values.
[0056] The present application study found that the double-sided thickness of the positive electrode active material layer will affect the energy density of the secondary battery, and the thickness will also affect the conduction resistance of lithium ions. When the double-sided thickness d of the positive electrode active material layer is further selected to be 190μm~230μm, a balance between energy density and lithium ion conduction resistance can be achieved, and the obtained secondary battery has excellent energy density and low internal resistance, and the obtained secondary battery has excellent cycle performance.
[0057] In one embodiment, the double-sided thickness dμm of the positive electrode active material layer is 200μm to 220μm. For example, it can be 200μm, 203μm, 205μm, 208μm, 210μm, 213μm, 215μm, 218μm, 220μm, or any two of them. The present application found that when the double-sided thickness d of the positive electrode active material layer is further selected to be 200μm to 220μm, the comprehensive performance of the secondary battery obtained is better.
[0058] In one embodiment, the capacity per unit area of the positive electrode sheet is C mAh / cm 2 5.5 mAh / cm 2 ~7mAh / cm 2 .
[0059] It should be noted that the test method for the capacity per unit area of the positive electrode sheet is: cut the positive electrode sheet into a button-type battery, charge and discharge it with a current of 0.33C, and finally calculate the capacity C per unit area of the positive electrode sheet.
[0060] Among them, the change of the capacity per unit area of the positive electrode plate can be achieved by adjusting the surface density of the electrode plate.
[0061] For example, the capacity per unit area of the positive electrode sheet is C mAh / cm 2 Up to 5.5mAh / cm 2 ~7mAh / cm 2 Any point value or any range value between two points, such as 5.5mAh / cm 2 、5.7mAh / cm 2 、5.9mAh / cm 2 、6.0mAh / cm 2 、6.2mAh / cm 2 、6.4mAh / cm 2 、6.6mAh / cm 2 、6.8mAh / cm 2 、7.0mAh / cm 2 The range value of one or both of them.
[0062] The present application found that the capacity per unit area of the positive electrode sheet will affect the energy density of the secondary battery. When further selecting the capacity per unit area of the positive electrode sheet C mAh / cm 2 5.5 mAh / cm 2 ~7mAh / cm 2 The energy density of the secondary battery obtained is higher.
[0063] In one embodiment, the capacity per unit area of the positive electrode sheet is C mAh / cm2 6.5 mAh / cm 2 ~6.9mAh / cm 2 . For example, it can be 6.5 mAh / cm 2 、6.6mAh / cm 2 、6.7mAh / cm 2 、6.8mAh / cm 2 、6.9mAh / cm 2 The present application has found that when the capacity per unit area of the positive electrode sheet is further selected to be 6.5 mAh / cm 2 ~6.9mAh / cm 2 When the secondary battery is used, the overall performance is better.
[0064] In one embodiment, the depth h μm of the grooves in the positive electrode active material layer is 30 μm to 60 μm.
[0065] It should be noted that the depth of the grooves in the positive electrode active material layer is tested by measuring the cross-sectional height using SEM.
[0066] Exemplarily, the depth hμm of the groove of the positive electrode active material layer may be any point value or any two point range values between 30μm and 60μm, for example, it may be one of 30μm, 33μm, 35μm, 38μm, 40μm, 43μm, 45μm, 48μm, 50μm, 53μm, 55μm, 58μm, 60μm or any two range values.
[0067] The research in this application found that the depth of the groove of the positive electrode active material layer will affect the wetting effect of the electrolyte, and also have a certain impact on the energy density of the secondary battery; when the depth hμm of the groove of the positive electrode active material layer is further selected to be 30μm~60μm, the secondary battery obtained has a higher energy density, better cycle performance, and lower internal resistance.
[0068] In one embodiment, the depth hμm of the groove of the positive electrode active material layer is 40μm to 55μm. For example, it can be a range of one or any two of 40μm, 42μm, 44μm, 46μm, 48μm, 50μm, 52μm, 54μm, and 55μm. The present application has found that when the depth h of the groove of the positive electrode active material layer is further selected to be 40μm to 55μm, the comprehensive performance of the secondary battery obtained is better.
[0069] In one embodiment, 25%≤Z≤65%, where Z=2h / d.
[0070] Exemplarily, Z can be any point value or any two point range values between 25% and 65%, for example, it can be one of or any two range values of 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%.
[0071] The present application study found that the relationship between the double-sided thickness of the positive electrode active material layer and the depth of the groove on the positive electrode active material layer will affect the wetting effect of the electrolyte and the energy density of the secondary battery. When the double-sided thickness of the positive electrode active material layer and the depth of the groove on the positive electrode active material layer further satisfy 25%≤2h / d≤65%, the comprehensive performance of the secondary battery obtained is better.
[0072] In one embodiment, 35%≤Z≤50%, where Z=2h / d. For example, Z can be 35%, 37%, 39%, 41%, 43%, 45%, 47%, 49%, 50%, or any two of them. The present application has found that when Z is further selected between 35% and 50%, the comprehensive performance of the secondary battery obtained is better.
[0073] In one embodiment, the negative electrode active material layer has grooves.
[0074] The research in the present application found that within the double-sided thickness range of the positive electrode active material layer provided in the present application, in addition to introducing grooves on the positive electrode active material layer, further introducing grooves on the negative electrode active material layer can be more conducive to shortening the bending distance of lithium ion migration, improving the diffusion efficiency of lithium ions, and thereby improving the fast charging capability of the secondary battery, reducing the internal resistance of the secondary battery, and improving the cycle performance and energy density of the secondary battery.
[0075] In one embodiment, the depth of the grooves on the negative electrode active material layer is 10 μm to 30 μm.
[0076] It should be noted that the depth of the groove on the negative electrode active material layer can be tested by using a laser thickness gauge.
[0077] Exemplarily, the depth of the groove on the negative active material layer may be any point value or any two point range values between 10μm and 30μm, for example, it may be one of 10μm, 13μm, 15μm, 18μm, 20μm, 23μm, 25μm, 28μm, 30μm or any two range values.
[0078] The present application has found that the depth of the grooves on the negative electrode active material layer affects the diffusion efficiency of lithium ions. When the depth of the grooves on the negative electrode active material layer is further selected to be 10 μm to 30 μm, the comprehensive performance of the secondary battery obtained is better.
[0079] In one embodiment, the grooves are distributed in the positive electrode active material layer or the negative electrode active material layer in a longitudinal direction, and the spacing between the grooves is 2 mm to 5 mm.
[0080] It should be noted that the test method for the groove spacing is: using SEM testing.
[0081] Exemplarily, the spacing of the grooves can be any point value or any two point range values between 2mm and 5mm, for example, it can be one of or any two range values of 2mm, 2.2mm, 2.4mm, 2.6mm, 2.8mm, 3mm, 3.2mm, 3.4mm, 3.6mm, 3.8mm, 4mm, 4.2mm, 4.4mm, 4.6mm, 4.8mm, and 5mm.
[0082] The research in this application found that the distribution state of the grooves and the spacing between the grooves will affect the tortuosity of the electrode, thereby affecting the diffusion capacity of lithium ions. When the grooves are further selected to be distributed longitudinally and the spacing is 2mm to 5mm, the resulting secondary battery has a higher energy density and better fast charging performance.
[0083] In one embodiment, the groove has a length of 20 mm to 90 mm and a width of 0.05 mm to 0.2 mm.
[0084] It should be noted that the testing method for the length and width of the groove is: using industrial CT to measure the length and width of the groove.
[0085] For example, the length of the groove can be any point value or any two point range values between 20mm and 90mm, such as 20mm, 30mm, 40mm, 50mm, 60mm, 70mm, 80mm, 90mm or any two range values. The width of the groove can be any point value or any two point range values between 0.05mm and 0.2mm, such as 0.05mm, 0.08mm, 0.1mm, 0.12mm, 0.15mm, 0.18mm, 0.2mm or any two range values.
[0086] The present application study found that the length and width of the groove affect the diffusion capacity of lithium ions. When the length and width of the groove are further selected within the above range, the resulting secondary battery has a higher energy density, a lower internal resistance and a better cycle performance.
[0087] In one embodiment, the positive electrode active material layer or the negative electrode active material layer can be introduced into the groove by laser etching; the depth, length and width of the groove can be changed by adjusting the parameters of the laser etching.
[0088] The present application has no particular restrictions on the parameters of laser etching, wherein the laser module power is 1000-2000W and the wavelength is 1064±2.5nm.
[0089] In one embodiment, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes lithium manganese iron phosphate and a ternary material.
[0090] In one embodiment, in the positive electrode active material, the mass percentage of the ternary material is ≤30%.
[0091] The present application study found that by introducing a suitable mass percentage of ternary materials into lithium manganese iron phosphate, it is possible to achieve good fast charging performance and energy density of the secondary battery while ensuring production costs.
[0092] In one embodiment, the ternary material includes lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide, wherein the lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide is Li a Ni b Co c X d Q e O2; wherein, 0.9≤a≤1.1, 0.3≤b<1, 0<c<1, 0<d<1, 0≤e≤0.1, b+c+d+e=1, X is Mn or Al, and Q is at least one of Zr, Al, Mn, Zn, Cu, Cr, Mg, Fe, V, W, Y, Nb, Ti, In, La, Ce, Sr, Sb, and B.
[0093] In one embodiment, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes graphite.
[0094] In one embodiment, the Dv50 particle size of the lithium manganese iron phosphate is 0.4 μm to 1.6 μm.
[0095] In one embodiment, the Dv50 particle size of the ternary material is 0.6 μm to 2 μm.
[0096] It should be noted that the test method for the Dv50 particle size of lithium manganese iron phosphate and ternary materials is: using a laser particle size analyzer to measure their particle size distribution.
[0097] Exemplarily, the Dv50 particle size of the lithium iron manganese phosphate may be any point value or any two point range values between 0.4μm and 1.6μm, for example, it may be one or any two range values of 0.4μm, 0.6μm, 0.8μm, 1.0μm, 1.2μm, 1.4μm, 1.6μm.
[0098] The research in this application found that the Dv50 particle size of lithium iron manganese phosphate will affect the lithium ion diffusion path and will have an impact on the specific surface area of the positive electrode active material. When the Dv50 particle size of lithium iron manganese phosphate is further selected to be 0.4μm~1.6μm, the resulting secondary battery has better rate performance and higher energy density.
[0099] Exemplarily, the Dv50 particle size of the ternary material can be any point value or any two point range values between 0.6μm and 2μm, for example, it can be one or any two range values of 0.6μm, 0.8μm, 1.0μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2μm.
[0100] The present application study found that the Dv50 particle size of the ternary material within the above range mixed with lithium iron manganese phosphate can effectively improve the rate performance and energy density of the secondary battery, and can also improve the production and processing performance of the positive electrode plate.
[0101] In one embodiment, the positive electrode active material layer further includes a conductive agent and a binder. The present application has no particular limitation on the selection of the conductive agent and the binder, and any known conductive agent and binder can be used.
[0102] In one embodiment, the negative electrode active material layer further includes a conductive agent and a binder. The present application has no particular limitation on the selection of the conductive agent and the binder, and any known conductive agent and binder can be used.
[0103] In one embodiment, the secondary battery further includes an electrolyte, and the electrolyte includes an organic solvent and a lithium salt. The present application has no limitation on the organic solvent and the lithium salt in the electrolyte, and any known organic solvent and lithium salt can be used.
[0104] Exemplarily, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate; the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.
[0105] In one embodiment of the present application, the present application proposes an electrical device, and the electrical device includes the secondary battery described in the present application.
[0106] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0107] Example 1
[0108] The present invention provides a secondary battery, wherein a method for preparing the secondary battery comprises the following steps:
[0109] (1) Preparation of positive electrode sheet
[0110] The positive electrode active materials (LMFP with a Dv50 particle size of 1 μm and NCM with a Dv50 particle size of 1.2 μm, the mass ratio of LMFP to NCM is 7:3, wherein NCM is specifically LiNi 0.6 Co 0.2 Mn 0.2 O2), a conductive agent (conductive carbon black SP), a binder (polyvinylidene fluoride), and a dispersant (polyvinyl pyrrolidone) are mixed in a mass ratio of 97:1.5:1:0.5, and a solvent N-methylpyrrolidone (NMP) is added, and the system is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector carbon-coated aluminum foil, and then transferred to an oven for drying, and then cold pressed to obtain a positive electrode active material layer with a thickness of d=220μm and a porosity of 45%, and then the cold-pressed positive electrode plate is etched with a laser to form grooves with equal spacing in the longitudinal direction on the surface of the plate (such as Figure 1 As shown, the depth h is 40 μm, the length is 90 mm, the width is 0.1 mm, and the spacing is 5 mm), and the positive electrode sheet has a unit area capacity of 6.9 mAh / cm 2 ;
[0111] (2) Preparation of negative electrode sheet
[0112] The negative electrode active material (graphite), the conductive agent (conductive carbon black SP), the thickener (sodium carboxymethyl cellulose), and the negative electrode plasticizer (dioctyl phthalate) are mixed in a mass ratio of 97:0.5:1.5:1, and deionized water is added as a solvent, and the mixture is stirred under the action of a vacuum stirrer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, and then transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode sheet;
[0113] (3) Preparation of electrolyte
[0114] The solvents FEC, EC, PC and EMC are mixed in a mass ratio of FEC:EC:PC:EMC=10:10:10:70 to obtain a mixed solution for use; at room temperature, in a glove box filled with argon, an electrolyte LiPF6 (12%) salt is added to the obtained mixed solvent, and the mixture is continuously stirred and cooled, and then a first additive 1.3-propane sultone (PS) and a second additive tris(trimethylsilyl) phosphate (TMSP) are added to obtain an electrolyte;
[0115] (4) Preparation of secondary batteries
[0116] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain a bare battery cell; the bare battery cell is assembled into a shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, formation, capacity division and other processes, a secondary battery is obtained.
[0117] Embodiments 2 to 4
[0118] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the porosity of the positive electrode active material layer is changed by adjusting the preparation of the positive electrode active material layer.
[0119] Embodiments 5 to 7
[0120] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the thickness of the positive electrode active material layer is changed by adjusting the preparation of the positive electrode active material layer.
[0121] Embodiments 8 to 10
[0122] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the capacity per unit area of the positive electrode sheet is changed by adjusting the preparation of the positive electrode active material layer.
[0123] Examples 11 to 13
[0124] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the depth of the groove of the positive electrode active material layer is changed by adjusting the preparation of the groove.
[0125] Embodiments 14 to 17
[0126] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the change of Y is achieved by adjusting the preparation of the positive electrode active material layer and the preparation of the groove.
[0127] Embodiment 18
[0128] The embodiment of the present application provides a secondary battery, which is different from the embodiment 1 in that the length of the groove is changed by adjusting the preparation of the groove.
[0129] Embodiments 19 to 20
[0130] The embodiment of the present application provides a secondary battery, which is different from the embodiment 1 in that the length of the groove is changed by adjusting the preparation of the groove.
[0131] Examples 21-22
[0132] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the change of the groove width is achieved by adjusting the preparation of the groove.
[0133] Embodiment 23
[0134] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the mass ratio of the positive electrode active material is changed by adjusting the positive electrode active material.
[0135] Embodiments 24 to 25
[0136] The embodiment of the present application provides a secondary battery, which is different from the embodiment 1 in that the particle sizes of lithium manganese iron phosphate and the ternary material are changed by adjusting the Dv50 particle sizes of the two.
[0137] Embodiments 26 to 28
[0138] The embodiment of the present application provides a secondary battery, which is different from the embodiment 1 in that the depth of the negative electrode groove is changed by adjusting the laser etching on the negative electrode active material layer (wherein the length of the negative electrode groove is 90 mm and the width is 0.1 mm).
[0139] Comparative Example 1
[0140] The comparative example of the present application provides a secondary battery, which is different from the embodiment 1 in that no groove is introduced into the positive electrode active material layer.
[0141] Comparative Examples 2-3
[0142] The comparative example of the present application provides a secondary battery, which is different from Example 1 in that the change of Y is achieved by adjusting the preparation of the positive electrode active material and the preparation of the groove.
[0143] The porosity ε of the positive electrode active material layer, the double-sided thickness d of the positive electrode active material layer, the capacity C per unit area of the positive electrode sheet, the depth h, length m, width n, and spacing l, Z of the groove of the positive electrode active material layer, the depth o, length p, width q, and spacing r of the groove of the negative electrode active material layer, the material of the positive electrode active material layer, the Dv50 of lithium manganese iron phosphate, and the Dv50 of the ternary material are shown in Tables 1 to 2;
[0144] Table 1 Parameters of secondary batteries
[0145]
[0146]
[0147]
[0148] Table 2 Secondary battery parameters
[0149]
[0150]
[0151] The performance of the secondary batteries prepared in the examples and comparative examples includes the following parts:
[0152] 1. Impedance of secondary battery: At 25±2°C, the battery obtained in the embodiment and the comparative example was charged at 0.5C to 3.65V, then discharged at 1C capacity for 30min, adjusted to 50% SOC, and then discharged at 2C constant current pulse for 10s and then charged for 10s. DCR was calculated as (voltage before pulse discharge – voltage after pulse discharge) / discharge current × 100%;
[0153] 2. Battery capacity in grams at different charging current rates of secondary batteries: At 25°C, the batteries prepared in the embodiment and the comparative example were charged to 3.65V at a constant current and constant voltage of 1C, and then discharged to 2.0V at a constant current of 0.5C. The charging and discharging system was cycled twice, and the average discharge capacity in grams was recorded as C1 (mAh / g). With the above charging system, the batteries were discharged to 2.0V at constant currents of 1C, 2C, 3C, and 4C, respectively, and the average discharge capacity in grams was recorded as Cn (mAh / g). The detailed data are shown in Table 3.
[0154] 3. Cycle performance of secondary batteries: At 25°C, the batteries prepared in the examples and comparative examples were charged at a 2C rate and discharged at a 1C rate, and full charge and discharge cycle tests were performed until the capacity of the battery was less than 80% of the initial capacity, and the number of cycles and DCR growth rate were recorded;
[0155] The results obtained are shown in Table 3;
[0156] Table 3 Performance test table of secondary batteries
[0157]
[0158]
[0159] As can be seen from Table 3, the present application introduces grooves in the positive electrode active material layer, and controls the positive electrode sheet to satisfy 32≤ε×(300-d) / 2+2×(12-C)+0.5h≤70, so that the secondary battery obtained has good cycle performance, high energy density and low internal resistance, and excellent comprehensive performance; specifically, the impedance R of the obtained secondary battery is 34.30mΩ or less, and the gram capacity obtained by testing at 0.5C, 1C, 2C, 3C, and 4C is 171.0mAh / g, 166.0mAh / g, 153.0mAh / g, 130.0mAh / g, 114.0mAh / g and above, respectively, the number of cycles is 1987 times or more, and the DCR growth rate is 48.3% or less;
[0160] It can be seen from Examples 1 to 26 and Comparative Example 1 that when grooves are not introduced in the positive electrode active material layer, the comprehensive performance of the obtained secondary battery is significantly reduced; it can be seen from Examples 1 to 26 and Comparative Examples 2 to 3 that when the positive electrode sheet satisfies 32≤ε×(300-d) / 2+2×(12-C)+0.5h≤70, the comprehensive performance of the secondary battery is significantly improved.
[0161] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; characterized in that: The positive electrode active material layer has a groove; The positive electrode sheet satisfies: 32≤Y≤70, Where, Y = ε × (300-d) / 2 + 2 × (12-C) + 0.5h; ε is the porosity of the positive electrode active material layer; dμm is the thickness of the positive electrode active material layer; C mAh / cm 2 is the capacity per unit area of the positive electrode; hμm is the depth of the grooves in the positive electrode active material layer.
2. The secondary battery according to claim 1, characterized in that: At least one of the following is met: (1) The porosity ε of the positive electrode active material layer is 25% to 50%; (2) The double-sided thickness dμm of the positive electrode active material layer is 190μm to 230μm; (3) Capacity per unit area of the positive electrode sheet C mAh / cm 2 5.5 mAh / cm 2 ~7mAh / cm 2 ; (4) The depth h μm of the grooves in the positive electrode active material layer is 30 μm to 60 μm.
3. The secondary battery according to claim 1, characterized in that: 25%≤Z≤65%, where Z=2h / d.
4. The secondary battery according to claim 1, characterized in that: The negative electrode active material layer has grooves.
5. The secondary battery according to claim 4, characterized in that: The depth of the grooves on the negative electrode active material layer is 10 μm to 30 μm.
6. The secondary battery according to claim 4, characterized in that: Taking the direction parallel to the positive electrode tab as the longitudinal direction, the distribution state of the grooves in the positive electrode active material layer or the negative electrode active material is longitudinal distribution, and the spacing between the grooves is 2 mm to 5 mm.
7. The secondary battery according to claim 4, characterized in that: The groove has a length of 20 mm to 90 mm and a width of 0.05 mm to 0.2 mm.
8. The secondary battery according to claim 1, characterized in that: The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes lithium manganese iron phosphate and a ternary material; The ternary material includes lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide, wherein the lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide is Li a Ni b Co c X d Q e O2; wherein, 0.9≤a≤1.1, 0.3≤b<1, 0<c<1, 0<d<1, 0≤e≤0.1, b+c+d+e=1, X is Mn or Al, and Q is at least one of Zr, Al, Mn, Zn, Cu, Cr, Mg, Fe, V, W, Y, Nb, Ti, In, La, Ce, Sr, Sb, and B; And / or, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes graphite.
9. The secondary battery according to claim 8, characterized in that: The Dv50 particle size of the lithium manganese iron phosphate is 0.4 μm to 1.6 μm; And / or, the Dv50 particle size of the ternary material is 0.6 μm to 2 μm.
10. An electrical device, characterized in that: The invention comprises the secondary battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Positive electrode for lithium-sulfur secondary battery having pattern, manufacturing method therefor, and lithium-sulfur secondary battery including same
CN113812017A
Sodium ion battery and preparation method thereof
CN113972393A
Electrode plate and lithium ion battery comprising same
CN114242933A
Secondary battery and electric device
CN118136918A
3D structured electrodes for electrochemical cells
WO2024064268A2
Cited By
A pole piece structure coupling surface embossing and internal porosity gradient of active layer and a preparation method thereof
CN122619712A